First-Line Autologous Stem Cell Transplantation for Mantle Cell Lymphoma: A Systematic Analysis and Treatment Recommendation - Liu, Hailing; Shi, Xiao; Fang, Huizi; Cao, Lei; Miao, Yi; Zhao, Xiaoli; Wu, Wei; Xu, Wei; Li, Jianyong; Fan, Lei (Frontiers in Oncology, 2022)
Background In the era of immunotherapy, autologous stem cell transplantation (ASCT) in first-line therapy in patients with mantle cell lymphoma (MCL) has been a controversial topic. This report aimed to explore the association between ASCT and MCL survival through a systematic review with meta-analysis. Methods We performed a systematic search of original articles published from inception to September 2021 using PubMed, MEDLINE, Embase, and Cochrane Library databases. Results We included studies that compared ASCT with non-ASCT consolidation in newly diagnosed transplant-eligible MCL. The endpoints were progression-free survival (PFS) and overall survival (OS). There were seven eligible studies (one randomized clinical trial, one prospective cohort study, and five observational studies) published between 2012 and 2021, in which the total number of participants was 3,271. In the non-intensive induction subgroup, patients with ASCT experienced a significant PFS but no OS benefit compared with those without ASCT. In the intensive induction subgroup, the PFS benefit from ASCT still existed but largely attenuated; no OS benefit was observed though only one study was suitable for evaluation. When compared to the rituximab maintenance arm, ASCT had a worse PFS and OS. Conclusions In the rituximab plus HiDAC era, the benefit of ASCT as a component of first-line treatment has been weakened. First-line maintenance strategy instead of ASCT seems worth exploring.